SAINS MODERN DALAM TAFSIR AL-MISBAH (Studi Penafsiran M. Quraish Shihab terhadap Q.S. Al-Baqarah: 26) - Iskandar iskandar (AR ROSYAD: Jurnal Keislaman dan Sosial Humaniora, 2022)
Al-Qur'an as a guide for life in understanding it required the sciences concerned with it. Al-Qur'an contains all knowledge and this is believed by every Muslim. The Qur'an is also a driving force for Muslims to research, seek and develop knowledge. The Qur'an is believed to cover all knowledge including science. However, in this case the scholars still differ. There are those who argue that the Qur'an cannot be combined with science or that it is not worthy like Sayyid Qutb. There are those who accept it by justifying it as a whole. There are also those who respond in a middle way, in the sense that when it is good and does not interfere with the meaning and purpose of the Qur'an, then it is permissible as proof of God's majesty. there are those who accept by justifying the whole like Quraish Shihab. Quraish Shihab is one of the scholars who has academic authority in interpreting and explaining the Qur'an, including those relating to the position of the Qur'an in the development of knowledge. which in this paper he proves with his interpretation of sura al-Baqarah: [26] In interpreting this verse he differs from other interpreters. It starts with mentioning how dangerous ants are which most people consider small and trivial, especially in this verse which is aimed at hypocrites. This interpretation is then correlated with the scientific opinion of the verse.